2006
DOI: 10.1097/01.ana.0000211007.94269.50
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Motor-evoked Potential Monitoring in Scoliosis Surgery: Comparison of Desflurane/Nitrous Oxide With Propofol Total Intravenous Anesthetic Regimens

Abstract: This is the first study comparing the use of desflurane and TIVA showing that both anesthetic regimens allowed successful intraoperative monitoring useage throughout the procedures. For MEP recording, the AH was the preferred muscle with a desflurane anesthetic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 19 publications
2
28
0
1
Order By: Relevance
“…During spinal surgery, monitoring MEP is a means of assessing the intraoperative integrity of corticospinal pathways [15]. Due to the limitation of the situations, intraoperative SSEP or MEPs was not monitored in our study.…”
Section: Discussionmentioning
confidence: 99%
“…During spinal surgery, monitoring MEP is a means of assessing the intraoperative integrity of corticospinal pathways [15]. Due to the limitation of the situations, intraoperative SSEP or MEPs was not monitored in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the choice and management of the anesthetic agents may impair the diagnosis of intraoperative spinal cord injury [23]. TcMEPs are significantly affected by the use of halogenated agents and nitrous oxide as well as the level of neuromuscular blockade because these agents affect the neural synaptic and axonal functional activities [23,24]. At an alveolar concentration (MAC) of 1.0 or higher, TcMEPs are often unobtainable.…”
Section: Discussionmentioning
confidence: 99%
“…10 tcMEP responses are affected and inhibited by anaesthetic agents like neuromuscular blockers, inhalation anaesthetics, and nitrous oxide; however, these responses are known not to be affected by the TIVA method. 11,12 When inhalation anaesthetics were investigated, studies demonstrated that sevoflurane and isoflurane in particular depress the amplitudes of tcMEPs in a dose-dependent manner. 13,14 In a prospective study of Lo et al conducted with desflurane, one study group was administered desflurane anaesthesia, the other was applied TIVA (propofol), and both groups were also given morphine when required; in this study, the proper tcMEP responses were recorded in both groups.…”
Section: Resultsmentioning
confidence: 99%